1997
DOI: 10.1080/09595239800187431
|View full text |Cite
|
Sign up to set email alerts
|

Work‐place alcohol and other drug testing: a review of the scientific evidence

Abstract: In this paper, scientific evidence for alcohol and other drug testing programs is compared to determine whether each approach is justifiable for improving work-place safety. Three types of studies are reviewed: laboratory, epidemiological and evaluation studies. Laboratory studies show that alcohol use decreases psycho-motor performance; however, for other drugs, some drugs deteriorate performance while others have little effect. Epidemiological studies in the work-place have not provided conclusive evidence t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 42 publications
0
24
0
Order By: Relevance
“…In fact, there may be no better way of obtaining such data, especially when assessing the context of substance use. Substance use behaviors are often hidden from potential collateral informants (Baldwin, 2000;Turkkan, 2000), collateral reports are subject to similar sources of error (Connors and Maisto, 2003;Del Boca and Darkes, 2003), and biologic tests (e.g., urine, hair, blood, saliva) cannot provide information regarding the context (on-the-job vs. off-the-job) in which substances were used (Frone, 2004;Macdonald et al, 1997;Normand et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, there may be no better way of obtaining such data, especially when assessing the context of substance use. Substance use behaviors are often hidden from potential collateral informants (Baldwin, 2000;Turkkan, 2000), collateral reports are subject to similar sources of error (Connors and Maisto, 2003;Del Boca and Darkes, 2003), and biologic tests (e.g., urine, hair, blood, saliva) cannot provide information regarding the context (on-the-job vs. off-the-job) in which substances were used (Frone, 2004;Macdonald et al, 1997;Normand et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…Third, and related to President Reagan's executive order, many companies test employees for illicit drugs but not for alcohol use. Because such drug tests cannot determine the time of use, they primarily detect use that has occurred off the job (Frone, 2004;Macdonald et al, 1997;Normand et al, 1994). This means that off-the-job use of illicit drugs identifi ed in pre-employment drug testing programs is used to deny employment to job applicants, and off-the-job use identifi ed in random drug testing programs might lead to sanctions or termination of employment among current employees.…”
Section: Supervisor Social Control and Employee Illicit Drug Usementioning
confidence: 99%
“…Two reviews of the literature indicate that alcohol does not play a substantial causal role in work injuries (Stallones and Kraus, 1993;Webb et al, 1994). Alcohol may not play an important role in work accidents because few people actually drink on the job in Ontario (Macdonald, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In a well-publicized case of Entrop versus Imperial Oil Ltd, both pre-employment and random drug testing were determined to be in violation of human rights laws because they cannot assess actual or future impairment on the job. Further strengthening this argument is that urine tests actually detect prior use rather than current impairment (Macdonald, 1997). Also, existing studies have certain methodological limitations and have not convincingly demonstrated that drug testing significantly reduces job accidents (Macdonald, 1997;Kraus, 2001).…”
Section: Drug Testing Programsmentioning
confidence: 95%
“…Governmental reasoning for promoting DTPs was influenced by political policies of the war on drugs, with all efforts aimed at eliminating drug use. However, in other countries, such as Canada, the only accepted reason for testing was the reduction in the likelihood of industrial accidents (Macdonald, 1997). DTPs follow the same objectives as those in the criminal justice system-enforcement, punishment, and deterrence.…”
Section: Drug Testing Programsmentioning
confidence: 99%